(untitled) (Research, Society and Development, 2022)
BMP´s are signaling proteins that belong to the Transforming Growth Factor-β (TGF-β) superfamily. These proteins promote the recruitment and differentiation of mesenchymal progenitor cells into bone forming cells, the osteoblasts and increase the rate of bone formation. The carrier systems to release rhBMP-2 to the action site are based on the use of free and soluble BMP incorporated into biopolymers such as collagen, gelatin, chitosan, hyaluronic acid and silk. The fused rhBMP-2-thioredoxin could be an interesting approach for new advances in the field of carrying systems of these growth factors. The fused protein thioredoxin can be useful as a coupling agent of BMP-2 to the carrier system, binding it to the surface of the matrix and it is one of the main aims of this work. The recombinant protein rhBMP-2 was produced by IPTG induction obtaining a soluble protein without the need for refolding process. The immobilization of rhBMP-2 at the surface of the TEMPO modified cellulose nanofibrils was indicated by FTIR spectroscopy. The cellular viability tests indicated increased proliferative behavior of both, C2C12 and stem cells from rats, when seeded in presence of rhBMP2 when compared to the free rhBMP2 substrate. The calcified extracellular matrix confirmed the increased activity of the rhBMP2-cellulose substrate, indicating the success of the proposed method. The cell proliferation assays indicated the method used to immobilize rhBMP2 onto the surface of the TEMPO modified cellulose was successful. The cells growth increased when compared to the reference sample free of rhBMP2.